2020
DOI: 10.21203/rs.3.rs-42340/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Brought to Life through Imagery” – Animated Graphic Novels to Promote Empathic, Patient-Centred Care in Postgraduate Medical Learners

Abstract: Background: Empathy levels decline through medical training. This has been associated with poor patient and physician outcomes, and strategies to combat this decline are increasingly recognized as critical aspects of medical education. The aim of this study was to qualitatively determine factors associated with empathy decline, and to assess the impact of a comics/graphic novel-based curriculum on enhancing empathy and a patient-centered approach to care in post-graduate medical learners. Methods: Fourth and f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Upon further scrutiny, we found that different interventions were being implemented either as a one‐off intervention or over a span of time (refer to Table 1). There were four articles which did not mention the duration of implementation 47–49,81 . Of these four articles, the results showed no significant change in empathy for two quantitative articles 47,48 and the other two were qualitative research 49,81 .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Upon further scrutiny, we found that different interventions were being implemented either as a one‐off intervention or over a span of time (refer to Table 1). There were four articles which did not mention the duration of implementation 47–49,81 . Of these four articles, the results showed no significant change in empathy for two quantitative articles 47,48 and the other two were qualitative research 49,81 .…”
Section: Resultsmentioning
confidence: 97%
“…A total of 44 articles (38 undergraduate and six postgraduate) 11,37,38,47–87 were reviewed. Interventions related to empathy have placed a higher emphasis on undergraduate as compared with postgraduate education.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the development of the era and technology demands the health sector to adapt and adjust when education is carried out [8], [9]. At present, technology has developed so rapidly that every mother in an urban area has a mobile phone and has been exposed to various shows on TV which make them have ideal figures that directly and indirectly influence their imagination [10], [11]. Moreover, in this pandemic era, the education service for pregnant women should be carried out still, without any socio-economic or location limitation because we still do not know when this pandemic will be over [12], [13].…”
Section: Introductionmentioning
confidence: 99%